Propuesta metodológica simplificada para la estimación del caudal dominante en ríos trenzados (2020)
The existence of various methodologies for estimating the dominant flow represents great variation in the results of this parameter. Due to the complexity in the dynamics of the rivers with braided characteristics, and the amount of information required for the correct estimation of the dominant flow, this document presents the research result of a methodological proposal to estimate the dominant flow in braided rivers, optimizing times and costs based on the minimization of required primary information.